PANGGILAN DAN PERUTUSAN AWAM KATOLIK DI TENGAH MASYARAKAT - Ola Rongan Wilhelmus (Bahasa Indonesia, 2019)
The call and mission of Catholic laymen in the Church and in the midst of society is often associated with the parable of the hired people in the Lord's vineyard (Mt 20: 1-16). Changes and various problems which have been occurring in the Church and in the community at all times urge the Catholic community to respond immediately. Catholic lay people are prohibited from becoming spectators when facing various problems and changes being occurred. The question is how and to what extent has the layman tried to live a family life and organize economic, political, legal, social, cultural activities, etc. according to God's plan and will?Answering the question, this paper intends to describe a number of main things, namely: first, lay call and mission in the community, second, Spontaneously answer of lay man to the call and mission of God; third, the perfection and novelty of life; and fourth, the call for holiness of life. This writing is inspired by the parable of the hired men in the vineyard (Mt 20: 1-8).